Test review: French examination of the College Scholastic Ability Test in Korea - Yoonhee Choi; Jihye Chun (Language Testing in Asia, 2022)
Abstract This study reviews the French examination of the College Scholastic Ability Test (CSAT), the most influential and highest-stakes test in Korea. The CSAT score has considerable influence on university admissions, and admission to a highly ranked university is generally a prerequisite for socioeconomic success. From this perspective, the significance of the CSAT is enormous. In general, the assessment is influenced by the goals and content of the curriculum, and it also plays an important role in curriculum implementation. In Korea, the national curriculum has been recently reformed. The main goal of the reformed French curriculum is to promote communicative skills and cultural literacy. However, the examination has been criticized for not uniformly or adequately evaluating overall communicative skills. Considering the importance of the CSAT and the interdependence of assessment and curriculum, the CSAT French examination has to be reviewed from the perspective of test quality. Due to its limited assessment of communicative skills, the validity of the French examination is debatable. The problem of low reliability also arises due to the uncertainty of assessment criteria and guidelines. Authenticity and interactiveness could be improved by avoiding fragmentary knowledge and memorization-oriented assessment. The negative washback effect needs to be addressed to resolve the low relevance of the curriculum to the test and the relatively low applicability of the CSAT French score in university admission policy.